Immunomodulatory role of Emblica officinalis in arsenic induced oxidative damage and apoptosis in thymocytes of mice - Singh, Manish K (BioMed Central, 2013)
BACKGROUND: Arsenic is widely distributed in the environment and has been found to be associated with the various health related problems including skin lesions, cancer, cardiovascular and immunological disorders. The fruit extract of Emblica officinalis (amla) has been shown to have anti-oxidative and immunomodulatory properties. In view of increasing health risk of arsenic, the present study has been carried out to investigate the protective effect of amla against arsenic induced oxidative stress and apoptosis in thymocytes of mice. METHODS: Mice were exposed to arsenic (sodium arsenite 3 mg/kg body weight p.o.) or amla (500 mg/kg body weight p.o.) or simultaneously with arsenic and amla for 28 days. The antioxidant enzyme assays were carried out using spectrophotometer and generation of ROS, apoptotic parameters, change in cell cycle were carried out using flow cytometer following the standard protocols. RESULTS: Arsenic exposure to mice caused a significant increase in the lipid peroxidation, ROS production and decreased cell viability, levels of reduced glutathione, the activity of superoxide dismutase, catalase, cytochrome c oxidase and mitochondrial membrane potential in the thymus as compared to controls. Increased activity of caspase-3 linked with apoptosis assessed by the cell cycle analysis and annexin V/PI binding was also observed in mice exposed to arsenic as compared to controls. Co-treatment with arsenic and amla decreased the levels of lipid peroxidation, ROS production, activity of caspase-3, apoptosis and increased cell viability, levels of antioxidant enzymes, cytochrome c oxidase and mitochondrial membrane potential as compared to mice treated with arsenic alone. CONCLUSIONS: The results of the present study exhibits that arsenic induced oxidative stress and apoptosis significantly protected by co-treatment with amla that could be due to its strong antioxidant potential.